Analisis Daya Saing Komoditas Jagung di Provinsi Gorontalo - Hestika Podomi; Angelina P. Tanda; Alvitra Nalole; Abdul Latif (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
According to the Central Statistics Agency for 2019-2021, the harvested area and area of ​​corn plants according to districts/cities, corn production comes from five districts, namely Bualemo district, Gorontalo district, Pohuwato district, Bone Bolango district, North Gorontalo district and Gorontalo city with a total of 377 432.00 ha in 2019, 304 945.00 ha in 2020, and 334 945.00 ha in 2021. By the end of 2022 it is predicted that 340,500 hectares or 27.38 percent of the entire Gorontalo land area will be planted with hybrid corn with a total harvest estimated at 1.61 million tons. This research uses qualitative methods, with primary data sources and secondary data. Corn productivity affects the net income of corn farmers apart from the selling price, where low productivity causes minimal harvest results, so the farmer's income is also low. Apart from that, fluctuations in corn prices are also an obstacle in increasing net income, when corn prices are high farmers get bigger profits. However, when the price of corn falls, farmers' income will also decrease. To increase the competitiveness of corn commodities in Gorontalo Province, it is necessary to invest in improving agricultural technology, opening wider market access, and providing greater government policy support. In this way, corn commodities in Gorontalo Province can become more competitive in both local and international markets.